The earned life : lose regret, choose fulfillment - Goldsmith, Marshall; Reiter, Mark (Currency, 2022)
"Discover the steps to earning your path to fulfillment and living without regrets--from the world-renowned executive coach and New York Times bestselling author of Triggers and What Got You Here Won't Get You There. Our lives exist on a continuum between two poles: fulfillment and regret. We invest enormous resources of time and energy into staying healthy, being recognized for our achievements, nurturing our relationships, and making money. When we make the right investments, we earn our lives: Our choices, risks, and efforts lead us to a rewarding outcome that we regard as fair and just, regardless of external validation. But how can we know if we're investing in the right things? How can we ensure that our "earned rewards" add up to an overarching sense of purpose in our lives? In The Earned Life, pioneering leadership coach Marshall Goldsmith shows us how to live our own lives--not someone else's version of them. The key to living the earned life, unbound by regret, requires our commitment to a habit of earning and connecting it to something greater than the isolated achievements of our personal ambition. Taking inspiration from Buddhism, Goldsmith implores readers to accept impermanence and avoid the Great Western Disease of "I'll be happy when...". He offers practical advice for shedding the obstacles, especially our failures of imagination, that prevent us from creating our own lives. With this book as their guide, readers can close the gap between what they plan to achieve and what they actually get done. Packed with illuminating exercises and stories from Goldsmith's storied career as a coach to some of the world's highest-achieving leaders, The Earned Life is a powerful road map for ambitious people seeking a higher purpose."--